Polarisasi Aliran Keagamaan Menyimpang Di Kabupaten Lombok Tengah - Azizah, Lutfatul; Fitriawan, Aidul; Fitriani , Windi (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2025)
This study analyzes social polarization toward religious groups considered deviant in Central Lombok, where movements such as Wahdatul Wujud, Islam Sasak, Shamsiyah, and Ahmadiyya have developed distinct religious interpretations. Their presence has raised concerns about doctrinal purity and social stability within the Muslim-majority community. Using Karl R. Popper’s theory of social polarization, this research explains the tendency of local society to adopt closed attitudes toward religious interpretive diversity. The study employs a qualitative approach, with data collected through field observations, in-depth interviews, and document analysis, which were analyzed thematically to capture prevailing social dynamics. The findings indicate that the emergence of these groups is driven by several factors, including low levels of religious literacy, the persistence of local cultural traditions, and dissatisfaction with formal da'wah practices. These conditions contribute to social division between groups defending orthodox Islamic teachings and those advocating greater religious freedom. The response of governmental and religious authorities particularly through heresy fatwas issued by the Indonesian Ulema Council (MUI) and intensified surveillance has further strengthened polarization. As a result, affected groups experience stigma, social exclusion, and occasional conflict, with the Ahmadiyya community facing the most severe pressure. The study concludes that strengthening inclusive religious education, promoting intergroup dialogue, and implementing strategies of religious moderation are crucial to reducing polarization and fostering social harmony in Central Lombok.